THE SPACE AND STRATEGIC STABILITY - Ekaterina Valeryevna Sazonova (Современная наука и инновации)
The article touches upon the issue of space militarization and transformation of strategic stability under the pressure of new threats for the international security. As a result it leads to the interdependence between the two processes.